Determinan Skor Pola Pangan Harapan di Indonesia Tahun 2022 - Wardana, Ardian Putra; Rahmawati, Iftina Ika; Dzunnurain, Zena Azzahra; Kartiasih, Fitri (Politeknik Statistika STIS, 2023)
One of the goals of the Sustainable Development Goals (SDGs) includes improving nutrition to overcome the many cases of hunger that occur in the world. Fulfillment of nutritional needs can be obtained by diversifying food. In Indonesia, food diversity is described by the Expected Dietary Pattern (PPH) score. In 2022, the PPH score experienced a substantial jump compared to the previous year, namely by 5.7 points. The purpose of this study was to analyze the factors that influence the PPH score and the condition of food diversity. The method used is cluster analysis with the Bicluster CC algorithm and multiple linear regression. The results of the study show that there are two regional groupings in Indonesia which are divided into areas with high food diversity in five provinces on Java Island and areas with low food diversity. The analysis that has been carried out also shows that there is a significant positive relationship between per capita spending and school enrollment rates on PPH scores.